The Puppet Concept - Trujillo, Sebastian (Auckland University of Technology, 2012)
This exegesis examines the practice-based interrelation between the technical rigging aspects of a CG character and the manner in which they affect the animator’s techniques and workflow. It discusses the construction and layering of essential artifacts a rig requires in order to meet the animator’s needs and inhibits the relationships between the two stages of the pipeline to exemplify its findings within a short film entitled Sam. This short comedy demonstrates various emotional stages throughout the frustration and stress overcoming a postman who’s postal truck gets stuck on some train tracks with a steam engine heading his way. Through methodological, theoretical and technical discussion, this project aims to deliver a clear understanding of the complex procedural tasks involved in creating an advanced character rig and how its flexibility, consistency and user-friendliness aids the workflow of an animator. Jason Osipa’s rigging methods are examined and applied to the pipeline to further develop the performance of the character. The project studies several approaches to animating actions based on the work habits of professional animator Jason Schleifer from DreamWorks Animation Studios, and studies how the animator’s workflow varies from shot to shot. It covers the progression of the critical planning, research and development of a character rig and the techniques used to produce convincing animation.
Keywords: Animation; Short film